2014
DOI: 10.1596/1813-9450-7070
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Caps around the World: Still Popular, but a Blunt Instrument

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…This is supported by Maimbo and Gallegos (2014), who observed that in South Africa, MFIs evaded caps by charging credit life insurance and other services, which reduced the transparency of the total cost of credit. They further stated that in Armenia, lack of clarity on how to calculate the interest rate led MFIs to impose fees and commissions not defined by the ceiling laws.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This is supported by Maimbo and Gallegos (2014), who observed that in South Africa, MFIs evaded caps by charging credit life insurance and other services, which reduced the transparency of the total cost of credit. They further stated that in Armenia, lack of clarity on how to calculate the interest rate led MFIs to impose fees and commissions not defined by the ceiling laws.…”
Section: Discussionmentioning
confidence: 80%
“…In situations where the scope of ceiling is not clear, financial institutions may give the impression of compliance with the ceiling but charge fees and commissions that are not considered part of the cost of the loan. In South Africa, some financial institutions evaded caps by charging credit life insurance and other services, which reduced the transparency of the total cost of credit and in Armenia, the lack of clarity on how to calculate the interest rate led banks and microfinance institutions to impose fees and commissions, thus avoiding the ceiling and reducing the transparency for consumers (Maimbo & Gallegos, 2014). Mohane et al (2002), argue that the consequence is people who want finance, but due to their circumstances do not qualify at the ceiling interest rate are denied access.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some financial sector authorities apply caps on interest rates on loans to protect consumers from excessive interest rates, support a specific industry or sector, or reduce the market power of credit providers. Generally speaking, interest rate caps can have market-distorting effects and reduce access to finance for some borrowers (Maimbo et al 2014).…”
Section: Product Regulationmentioning
confidence: 99%